1953
DOI: 10.1103/physrev.89.343
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in Energy of the Neutrons from the Interaction of 14-Mev Neutrons with Some Elements

Abstract: The neutron spectra from the interaction of 14-Mev neutrons with a number of elements have been determined by nuclear plate techniques. The plates were exposed to neutrons from the bombardment of a Zr-T target by 200-kev deuterons when the target was as nearly as possible isolated from all scattering material and when the target was surrounded by a spherical shell of the element to be investigated. The variation of F(E n ), the number of emitted neutrons per unit energy interval with energy (E n ), appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1956
1956
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Therefore, both formulas can be used from the practical point of view to obtain the energy spectra with their appropriate values for the parameter. Equation ( 3 ) has been used frequently in the past.…”
Section: Figmentioning
confidence: 99%
“…Therefore, both formulas can be used from the practical point of view to obtain the energy spectra with their appropriate values for the parameter. Equation ( 3 ) has been used frequently in the past.…”
Section: Figmentioning
confidence: 99%
“…Figure 3 theoretically and are experimentally verified, but there is no direct cosmic-ray information about the higher-energy neutron source spectrum. Neutron spectra have been measured by Graves and Rosen [1953], using 14-Mev neutrons bombarding various elements, and by Gross [1956], using 190-Mev protons bombarding various elements. These authors find that below 3 or 4 Mev the neutrons are clearly identified as evaporation neutrons but that above 4 Mev the yield of neutrons is higher than expected from evaporation, and that the neutrons come off preferentially forward.…”
Section: Zoom a Neutron-diffusion Code [Stuart Canmentioning
confidence: 99%
“…The energetic 14-MeV neutrons from the DTreaction would induce fast fission in the blanket. Subsequently, the neutrons could be captured in 238 U to form 239p u or in 6 Li to breed tritium. It was assumed that a proper arrangement of uranium and supporting structure would lead to a net multiplication of the incident neutrons.…”
Section: A Early Studiesmentioning
confidence: 99%